Banking in Africa: financing transformation amid uncertainty - European Investment Bank (EIB) (European Investment Bank (EIB), 2020)
In its fifth edition, this report focuses on recent developments in Africa's banking sectors and the policy options for all stakeholders. The study of banking sectors across all African sub-regions includes the results of the EIB survey of banking groups operating in Africa. Three thematic chapters address challenges and opportunities for financing investment in Africa: - Investing sustainably in Africa's cities; - Mobilising agricultural value chain financing in Africa: why and how; - Remittances and financial sector development in Africa.
Keywords: 330; Africa; agricultural policy; bank; banking system; development aid; economic integration; European Investment Bank; financial services; financial stability; financing; new technology; report; Bank; Branchenentwicklung; Afrika